Private and Public Debt - Vratilav Izák (European Financial and Accounting Journal, 2014)
In the paper we provide some empirical evidence of the development of private debt to GDP ratio in the sample of 18 EU Member States. We use detailed national accounts published regularly by the OECD-financial assets and liabilities by institutional sectors (flow of funds). The ratio of private to public debt culminated mainly in the year 2007 and since 2008 this ratio has the tendency to decline. Spillovers across private and public debt have revealed mainly a mutual dependency. Cross-country differences have been discovered in both households and non-financial corporations debt.
Keywords: D9; E6; H3; 650; Private debt; Public debt; Flow of funds